DEVELOPMENT OF DRIBBLING BASIC TECHNIQUE SKILL OF STUDENTS OF PSTS TABING PADANG FOOTBALL SCHOOL - Emral Emral; James A.P. Tangkudung (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The objective of this research is to create dribbling learning models and to experiment dribbling training models of playing football for students of Football School (FBS) of PSTS Tabing Padang. This research was conducted at the FBS using the football experts and the students as the subjects. The research conducted was development model of Borg and Gall. The validation data of the experts were collected through field notes and questionnaires, analyzed by descriptive analysis technique. The dribbling basic technique skill of football was analyzed by using t-test. The research findings are as follows: (1) football dribbling basic technique skill which were developed based on the training principles and training methodology, starting from the simple one and ended by game situation, (2) the training model is very effective to be used in the process of training, (3) it was empirically proved that the model was effective. Keywords: training model; dribbling; playing football.